Homologous Recombination Repair Gene Variants and Outcomes Among Patients With Prostate Cancer Treated With Poly (ADP-ribose) Polymerase Inhibitors. (27th April 2022) - Price, Meghan J.; Vashistha, Vishal; Winski, David; Kelley, Michael J.; Bitting, Rhonda L.; Montgomery, Bruce
Abstract : PURPOSE: Poly ADP-ribose polymerase inhibitors (PARPi) are used for patients with advanced prostate cancer bearing alterations in homologous recombination repair (HRR) genes. We sought to characterize HRR gene variants and describe real-world outcomes for patients on PARPi. METHODS: The US Department of Veterans Affairs' National Precision Oncology Program's database was reviewed to identify patients who underwent somatic DNA sequencing and were prescribed a PARPi before May 15, 2020. Somatic and germline variants within HRR genes were reported, and pathogenicity was reviewed via OncoKB. In patients treated with PARPi for > 4 weeks, the rate of those achieving a 30% decrease in prostate-specific antigen (PSA30) and composite progression-free survival (PFS) were compared between patients bearing pathogenic variants of BRCA2 and patients without these variants using Mann-Whitney and log-rank tests, respectively. RESULTS: Forty-eight patients bearing 67 total HRR gene variants were prescribed PARPi for prostate cancer. Twenty-one patients (43.8%) were found to have at least one pathogenic HRR gene variant. Eight (16.6%) were referred to genetic counseling, and five (10.4%) were ultimately confirmed with germline variants. The median PFS was 4.0 months, and PSA30 was 25.6% (11 of 43) for all 43 evaluable patients. Patients with pathogenic BRCA2 variants (n = 13) had higher PSA30 (69.2% v 4.0%; P < .001) and longer PFS (7.2 v 2.8 months; P = .0291) than those without. CONCLUSION: In a real-world setting, heavily pretreated patients with prostate cancer and pathogenic BRCA2 variants have a significant PSA response rate and a PFS > 7 months with PARPi. This work emphasizes the importance of determining pathogenicity and origin of HRR alterations to better inform clinical treatment decisions and highlights the need for provider education and other decision support tools. Abstract :